Pengaruh Merger Bank Syariah Terhadap Kompetisi dan Efisiensi Industri Perbankan Syariah di Indonesia: Studi Kasus pada PT. Bank BRI Syariah Tbk, PT. Bank Syariah Mandiri, dan PT. Bank BNI Syariah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the impact of the merger of Islamic banks on competition and efficiency within the Islamic banking industry in Indonesia. The research focuses on the merger of PT Bank BRI Syariah Tbk, PT Bank Syariah Mandiri, and PT Bank BNI Syariah, which resulted in the establishment of Bank Syariah Indonesia (BSI). The analysis is conducted to assess whether the merger has strengthened market competition and improved operational efficiency in the industry. Using quantitative methods and secondary data, this study evaluates the level of competition through market concentration ratios and efficiency through financial performance indicators before and after the merger. The findings of this research are expected to provide valuable insights for policymakers, industry players, and stakeholders in formulating strategies for sustainable growth in the Islamic banking sector.